Advancing precision diagnostics: minimally invasive approaches for understanding the role of brain-limited somatic mutations in pediatric drug-resistant epilepsy - Fariyike, Olubunmi A.; Narayan, Nishanth; Liu, Hilary Y.; Sanchez, Danielle R.; Phillips, H. Westley (Frontiers in Surgery, 2025)
For the one-third of epilepsy patients whose disease is refractory to medical therapies, the social, economic, and developmental consequences are often devastating and lifelong. This has sparked great interest in the elucidation of the genetic drivers of epilepsy for the discovery of precision therapies. Over the past 30 years, tissue derived from standard-of-care open resections has provided genetic material for a wealth of research on the genetic mechanisms of epileptic disease. One of the most important findings of this research is the presence of pathogenic brain-limited somatic mutations; however, many patients who would benefit from genetic analysis are not surgical candidates. Further, as minimally invasive techniques such as laser ablation and neuromodulation become increasingly indicated, access to surgically resected brain tissue may become more limited, posing challenges for the research and diagnostic advancements that have traditionally relied on such samples. Fortunately, two minimally invasive methods for obtaining brain-derived genetic material have been developed in recent years. Both cell-free DNA isolated from cerebrospinal fluid and DNA extracted from microbulk tissue adherent to stereo-EEG (sEEG) electrodes have demonstrated sufficient quantity and quality for identification of brain-limited somatic variants. Both techniques have important advantages over surgically obtained bulk-brain tissue and hold promise as new leading avenues of genetic epilepsy research. This article provides a general overview of brain-limited somatic variants in pediatric drug-resistant epilepsy, with a specific focus on the evidence for the use of electrode- and cerebrospinal fluid-derived DNA. We also detail the specific advantages and disadvantages of these minimally invasive techniques as compared to the use of traditional, resection-derived bulk tissue.